Optimalisasi Kinerja Guru Dalam Mengembangkan Keterampilan Literasi Sains Kelas IV SDN Karang Tengah 07 - Encep Andriana; Aceng Hasani; Lukman Nulhakim; Putri Nabilah Rasendriya (Jurnal Elementaria Edukasia, 2023)
Teachers have an important role in creating quality learning that involves aspects of knowledge, attitudes and skills. one of the skills that support is science literacy skills. However, this skill is rarely possessed by students, so the author tries to analyze how optimizing teacher performance can develop this literacy skill. The method used is descriptive qualitative, where the instruments used are observation and interviews conducted at SDN Karang Tengah 07. The results obtained in this data collection are optimizing teacher performance in three processes, namely in planning by preparing teacher knowledge related to science literacy skills and paying attention to the needs of students and learning objectives, implementation by inserting science literacy in reading time activities and the learning process, and finally evaluation by providing positive affirmations.